Exploring Debates over "Boys Love" Media in the Philippines: from Misogynistic Backlash to Queer Emancipation - Santos, Kristine Michelle L (Archīum Ateneo, 2024)
As a genre originally emerging from Japanese women’s popular culture and developing into a transnational phenomenon, debates over “Boys Love” (BL) media have increased in recent years. Within this article, we explore debates over BL through a case study of its reception in the Philippines, situating our analysis within the broader context of the Philippines’ heteropatriarchal culture. Drawing upon critical discourse analysis of traditional and new media discussions responding to the rise of BL fandom in the Philippines and qualitative interviews with 31 LGBTQ+ fans of BL, we reveal tensions between those who view BL positively and negatively. Through a feminist and reparative queer reading of our data, we contrast cisgender gay men’s dismissal of the genre as always already problematic due to its emergence from women’s culture with LGBTQ+ Philippine fans’ positioning of BL as an emancipatory media genre that combats homophobia. Ultimately, we argue that attempts by certain critics in the Philippines to downplay the queer emancipatory potentials of BL emerges from a misogynistic rejection of the contributions of women to Philippine queer culture. We conclude by calling for a more nuanced appreciation of BL’s queer interventions which recognises the genre’s deconstructive force.